(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the level of psychological stress and to identify several associated factors among patients with lumbar spine trauma receiving treatment at Viet Tiep Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 102 patients with lumbar spine trauma treated at Viet Tiep Friendship Hospital from November 2025 to March 2026. The Brief Symptom Rating Scale-5 (BSRS-5) was used to assess the level of psychological distress. Results: The proportions of patients with mild, moderate, and severe psychological distress were 21.6%, 10.8%, and 3.9%, respectively. Factors associated with the level of psychological distress among patients included having someone to confide in when feeling sad, comorbidities, and duration of treatment. Conclusion: The prevalence of psychological distress among patients with lumbar spine trauma was relatively high. Factors such as emotional support, comorbidities, and treatment duration were associated with the level of psychological distress, suggesting the need for appropriate interventions to comprehensively improve the effectiveness of patient care.